(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to examine and analyse the influence of transformational leadership and organisational culture on employee performance at SMAN 11 Tanjung Jabung Barat. This study was motivated by the importance of the role of leaders and organisational culture in encouraging improved performance among civil servants. Data collection was conducted by distributing questionnaires to 12 respondents, all of whom were civil servants. The results of this study indicate that the variables of Transformational Leadership and Organisational Culture simultaneously have a significant effect on Employee Performance. Partially, the Organisational Culture variable obtained a significance value of 82.67%, strongly agree, which means it has a significant effect on Performance. The Transformational Leadership variable also showed a significant effect on Performance with a significance value of 84.76% strongly agree. Thus, it can be concluded that improving organisational culture and implementing effective transformational leadership can significantly improve employee performance.